UPAYA MENINGKATKAN KETERAMPILAN BERBICARA MELALUI STORYTELLING PADA PEMBELAJARAN BAHASA INDONESIA UNTUK SISWA DI SEKOLAH DASAR - Erillia, Risky (Jurnal Sintaksis, 2025)
This study used the classroom action research (CAR) method. This classroom action research refers to the model developed by Kemmis and McTaggart, which consists of four main stages: (a) planning, (b) implementation, (c) observation, and (d) reflection. These four stages are carried out repeatedly in two or more cycles until significant improvements in speaking skills are achieved. The research subjects were 25 fourth-grade students at SD IT Hamas, consisting of 18 girls and 7 boys. The object of the study was storytelling. Data collection techniques included observation, questionnaires, and documentation. Data analysis used descriptive qualitative techniques. The results showed that in cycle 1, students' abilities were still low, with an average completion rate of 39%. While in cycle 2, there was a significant increase to 78%. This indicates that the implementation of appropriate learning strategies and intensive mentoring can help students express ideas, construct sentences coherently, and improve pronunciation and expression when speaking. Thus, the structured, gradual learning process has a positive impact on the development of students' speaking skills in elementary grades.